Qualidade do solo em sistemas convencional e conservacionista na produção de milho verde nos tabuleiros costeiros - Santos, Jusimara de Andrade (2023)
The cultivation of green corn represents an activity of great economic and social value for family farmers in the state of Sergipe. However, inadequate soil management has generated destruction of soil structure, reduced productivity and profitability of crops, linked to environmental degradation. Physical attributes such as density, mechanical resistance to penetration, aggregate stability directly linked to the stability of the soil structure, as well as the organic carbon content are important parameters that signal the impacts of soil use and management. The objective of this work is to evaluate the physical parameters of the soil, the content and stock of organic carbon in the soil, the structural quality, the vegetation cover of the soil and the productivity of green corn in a Red Yellow Argisol of the Coastal Tableland under different soil preparations. soil and antecedent cultures in a long-term experiment (22 years) in the city of São Cristóvão-SE (10°55'24''S and 37°11'57''W). For that, the physical parameters of the soil were determined: density and mechanical resistance to penetration (RMP); the structural quality of the soil (Qe); the Vegetation Cover Index (ICV) and the agricultural productivity of green corn in three soil preparation systems (Conventional Cultivation-CC; Minimum Cultivation-CM and Direct Sowing-PD) associated with four antecedent crops (cowpea (Vigna unguiculata ), sunn hemp (Crotalaria juncea), pigeonpea (Cajanus cajan) and millet (Pennisetum glaucum)). Yield was determined in the number of commercial ears of green corn produced and other productivity parameters such as number of plants, weight, diameter and length of commercial ears; the stability of aggregates was determined by the standard method of Yoder (1936) adapted; the Qe was determined following the adapted method of Ball (2007) and the ICV was determined following the method described by Stocking (1988) with adaptations. The results indicated that the CM system had a greater number of commercial ears, when compared to the CC and PD, and the highest productivity was observed when the CM was combined with the previous culture of Guandu/CM (12,722 ears/ha) under the treatment nitrogenous. The lowest soil density was verified in the CM associated with Guandu for the two depths (0-10 and 10-20 cm) from the soil to the Cowpea step, which also presented the lowest density value. Cowpea/CM showed the lowest mechanical resistance to penetration (0.44 MPa) while the highest values were obtained in Crotalaria/CC interaction (0.83 MPa). It was also verified that the cultivation systems altered the COS concentration, conferring different Qe. The best Qe was conferred by PD/Crotalária. The results show that the use of conservationist systems should be prioritized when aiming at long-term agricultural sustainability, not recommending conventional tillage, as this was considered unsustainable when associated with low structural quality and agricultural productivity.